2017
DOI: 10.1089/lap.2017.0190
|View full text |Cite
|
Sign up to set email alerts
|

Is Portomesenteric Vein Thrombosis After Laparoscopic Sleeve Gastrectomy Related to Short-Course Prophylaxis of Thromboembolism? A Monocentric Retrospective Analysis About an Infrequent but Not Rare Complication and Review of the Literature

Abstract: PMVT is an infrequent but not rare complication in patients who undergo LSG. Short-course antithrombotic prophylaxis (<10 days) could increase the risk of this complication. The authors recommend a postoperative prophylaxis with sodium enoxaparin 40 mg sc once a day for 4 weeks. PMVT mortality in patients who undergo LSG is lower than other causes of portal vein thrombosis (hepatic cirrhosis, tumors, myeloproliferative disorders, etc.) If risk factors for PMVT are present preoperatively, the authors recommend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…In 2014, SG was the most performed BS, comprising >50% of all primary BS in 2016, and had the highest increase rates in recent years [ 36 , 77 , 78 ]. Post-SG PMVT incidence is 0.37%–1% and is increasing with SG's popularity [ 79 ]; and a 0.1%–1.81% PMVT incidence has been observed post-BS including laparoscopic BS [ [80] , [81] , [82] ]. Research has reported a 1.61% PMVT mortality rate [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2014, SG was the most performed BS, comprising >50% of all primary BS in 2016, and had the highest increase rates in recent years [ 36 , 77 , 78 ]. Post-SG PMVT incidence is 0.37%–1% and is increasing with SG's popularity [ 79 ]; and a 0.1%–1.81% PMVT incidence has been observed post-BS including laparoscopic BS [ [80] , [81] , [82] ]. Research has reported a 1.61% PMVT mortality rate [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Post-SG PMVT incidence is 0.37%–1% and is increasing with SG's popularity [ 79 ]; and a 0.1%–1.81% PMVT incidence has been observed post-BS including laparoscopic BS [ [80] , [81] , [82] ]. Research has reported a 1.61% PMVT mortality rate [ 82 ]. It is unclear if this increased incidence is due to the increasing frequency of LSG, or if LSG carries independent PVT risk [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PMVT in LSG was first reported in 2009 by Berthet et al [7]. Caruso et al [8] reported only one PMVT case in their 2854 patients whose underwent LSG for morbid obesity. They also revealed 62 cases of PMVT after LSG with a prevalence of 0.52% (ranging from 0.2 to 1.81%) and a mortality rate of 1.61% in selected 18 studies [8].…”
Section: Case Reportmentioning
confidence: 98%
“…Caruso et al [8] reported only one PMVT case in their 2854 patients whose underwent LSG for morbid obesity. They also revealed 62 cases of PMVT after LSG with a prevalence of 0.52% (ranging from 0.2 to 1.81%) and a mortality rate of 1.61% in selected 18 studies [8]. The incidence of PMVT is 0.19% in all obesity surgery and 0.28% in LSG in our institution without any mortality.…”
Section: Case Reportmentioning
confidence: 99%